Carbon monoxide releasing molecule enhances coagulation and decreases fibrinolysis in canine plasma exposed to Crotalus viridis venom in vitro and in vivo. Issue 4 (31st May 2019) - Johnson, Tyler E.; Wells, Raegan J.; Bell, Amy; Nielsen, Vance G.; Olver, Christine S.
Abstract: Carbon monoxide releasing molecule‐2 (CORM‐2), an emerging therapeutic in human medicine, enhances plasmatic coagulation and attenuates fibrinolysis in vitro in human, rabbit and horse plasma and ameliorates hypocoagulation and hyperfibrinolysis secondary to venom exposure in human plasma in vitro. Fibrinogenases in rattlesnake venom cause decreased clot strength, and in the presence of tissue plasminogen activator (tPA) in vitro, a markedly increased rate of clot lysis. CO interacts with a haem group on fibrinogen, changing its configuration so that the fibrin clot is strengthened and more resistant to fibrinolysis. We hypothesized that CORM‐2 enhances coagulation and attenuates fibrinolysis in canine plasma exposed to C viridis venom. We measured the effects of C viridis venom on clot strength, rates of coagulation and fibrinolysis in both pooled canine plasma and plasma from individual naturally envenomed dogs, with and without CORM‐2, using thromboelastography (TEG). We tested venom effects on coagulation using tissue factor (TF) activated TEG and on both coagulation and fibrinolysis using TF‐activated TEG with added tPA. We found that 17.9 µg/mL of venom causes a mean 26.4% decrease in clot strength, a 61.8% decrease in maximum rate of thrombus generation, 75% faster clot lysis, a 226% increase in maximum rate of lysis and a 92% decrease in total clot life span (CLS). CORM‐2 ameliorated these effects, increasing CLS in the presence of venom by 603%. Additionally, we showed that CORM‐2 has similar effects in vitro on plasma from naturally envenomed dogs, showing promise as an adjunct therapy for snake envenomation.